The interrelation of time and tense in English Grammar - Tillayev Zafar Akmalovich (Research Parks Publishers, 2021)
The relationship between utterance time and the time of the situation described may be direct as in the case of Absolute tenses like the past tense or indirect as in the case of relative tenses like the future perfect (e.g. I will have left [by the time you read this letter]), in which the leaving events is represented as in the past relative to a point that is in the future relative to utterance time (the point at which the letter is read). Like other linguistic reference point that are anchored in the here and nouns the temporal zero point can, under the appropriate conditions, be identified with times that the time of speaking or writing. One such case is that in which writer uses the time of message interpretation, rather than the time of message construction, as the zero –point. For example, a not writer may choose the formulation I’m across the hall rather than I will be across the hall. The shifting of the temporal zero –point also occurs is subordinate clauses both temporal and conditional, as in e.g., When/ if you have finished your test [raise your hand]. Here, a present perfect predication is used despite the fact that is reference point is located in a (hypothetical) future rather than at the time of speaking.